Halal product checker: real time ingredient verification application using mobile text scanning - Abd Rahim, Adam Putra (2025)
The Halal Product Checker: Real-Time Ingredient Verification Application Using Text Scanning is an OCR (Optical Character Recognition) technology-based mobile application created to assist Muslims in ascertaining whether the ingredients in foods are halal. It scans product labels to check ingredients and compares them with a halal ingredients database in real time. This project has adopted the Agile Scrum methodology, which emphasizes iterative refinement and continual improvement in product quality. Completion of the application has been achieved and System Usability Scale (SUS) testing indicated high user satisfaction. Users reported an enhancement in their confidence to make halal food choices, with speedier decisions and accurate real-time verification. Results confirmed the app’s effectiveness in streamlining the halal verification process, solving problems such as ambiguous ingredient lists and the absence of real-time verification tools in other systems. Although the app met its targeted goals, limitations remain such as offering low-quality images and limited OCR accuracy, restricted database coverage, and lacking comprehensive cross-referencing. Further revisions will aim on improving the lack of multilingual algorithms and broadening the database to make the app accessible to users worldwide. All in all, The Halal Product Checker App demonstrates its reliability and efficacy as an aid to the user’s confidence and decision-making in selecting halal food.